Analysis of the Effect of Stock Split on Abnormal Stock Return and Share Liquidity - Jerri Priatno; Freddy Freddy (Green Publisher Indonesia, 2021)
Strong companies will not be too affected by news issues about stock splits, but several other companies that do stock splits actually experience a decline in demand for their shares. This study aims to analyze the effect of stock splits on abnormal stock returns and stock liquidity. In this study, the authors use quantitative research methods with a descriptive research approach, because there are variables to be examined and the relationship aims to describe the characteristics or behavior of a population in a systematic and accurate way regarding the relationship between the variables to be studied. The population in this study are companies listed on the Indonesia Stock Exchange, namely companies that carried out stock splits in 2019. Based on the results of research, the authors draw the following conclusions: Based on statistical tests on abnormal returns, it was found that market reactions occurred during the day after the stock split, the first day until the fourth day after the stock split. Based on the results of the different tests on Abnormal Returns before and after the stock split, it shows that there is a significant difference between the returns before and after the stock split. Based on the results of the different tests on the average TVA before and after the stock split, it shows that there is a significant difference between TVA before and after the stock split.